Peningkatan Kesadaran Anti-Bullying Melalui Teknik Sosiodrama Pada Siswa - Tita Astria (Peneliti.net, 2023)
In the school environment, there are often acts of pushing friends to the ground, hitting friends, mocking/insulting/ making fun of friends, harassing either directly or through social media, even to isolate, intimidate and ignore their friends. The research objective is to increase anti-bullying awareness through sociodrama techniques. The research method used is action research. The results showed that the sociodrama technique group guidance service was able to increase students' anti-bullying awareness. This is evidenced by the increasing awareness of anti-bullying students after receiving sociodrama technical group guidance services through two cycles of 4 meetings. The results showed a significant increase. Anti-bullying awareness was still low before receiving sociodrama technical group guidance services, there was an increase after receiving sociodrama technical group guidance services cycle I, and increasing after receiving sociodrama technical group guidance services in cycle II.